The influence of Metaverse Virtual Tourism on traveler loyalty to virtual destinations: A Systematic Literature Review - Suwandi S Sangadji; Dedy Iswanto (JUSTE (Journal of Science and Technology), 2025)
This research aims to explore the influence of Metaverse Virtual Tourism on traveler loyalty to virtual destinations and how technologies such as Virtual Reality (VR) and digital twin can enhance tourism experiences in virtual worlds. Using the PRISMA 2020-based Systematic Literature Review (SLR) approach, this research analyzes articles from the Scopus database using the Watase Uake tool that examine the application of Metaverse in the tourism industry. The results show that the immersive experience created by Metaverse, through VR and digital twin technologies, has a positive impact on tourists' intention to visit physical destinations. In addition, the digital era strengthens the effectiveness of Metaverse Virtual Tourism by using social media, e-commerce, and digital content personalization, which increases tourist engagement and loyalty. However, key challenges in the implementation of Metaverse Virtual Tourism include the acceptance of technology among certain age groups, especially older generations, as well as greenwashing issues in destination promotion. This study suggests that further research be conducted to optimize the design elements in Metaverse Virtual Tourism and overcome existing obstacles related to technology adoption and non-uniform regulations.